2020
DOI: 10.1097/sla.0000000000003017
|View full text |Cite
|
Sign up to set email alerts
|

Do Patients With Inflammatory Bowel Disease Have a Higher Postoperative Risk of Venous Thromboembolism or Do They Undergo More High-risk Operations?

Abstract: Postoperative VTE risk varies widely by the operation performed, and a diagnostic indication of CD or UC does not play a role. Extended duration VTE prophylaxis should be considered in all patients undergoing high-risk operations, regardless of their underlying diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 30 publications
1
30
0
Order By: Relevance
“…The three operations that were associated with the highest rate of postoperative VTE included TAC, either laparoscopic or open, segmental colectomy with colostomy and mucous fistula creation, and open TPC .Six studies identified open operations as an independent risk factor for postoperative VTE events . Similarly, six studies identified emergent operations as an independent risk factor . Longer operative time (defined as longer than 4 h) was also identified as a significant risk factor in four studies .Overall, it is clear that colorectal operations performed for IBD are associated with high risk of postoperative VTE, perhaps even independent of disease pathophysiology. What patient risk factors affect the rates of VTE in IBD patients undergoing colorectal surgery?The patient characteristics most commonly associated with increased postoperative VTE risk are age over 65 years (eight studies), chronic steroid use (eight studies) and obesity (six studies) .…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…The three operations that were associated with the highest rate of postoperative VTE included TAC, either laparoscopic or open, segmental colectomy with colostomy and mucous fistula creation, and open TPC .Six studies identified open operations as an independent risk factor for postoperative VTE events . Similarly, six studies identified emergent operations as an independent risk factor . Longer operative time (defined as longer than 4 h) was also identified as a significant risk factor in four studies .Overall, it is clear that colorectal operations performed for IBD are associated with high risk of postoperative VTE, perhaps even independent of disease pathophysiology. What patient risk factors affect the rates of VTE in IBD patients undergoing colorectal surgery?The patient characteristics most commonly associated with increased postoperative VTE risk are age over 65 years (eight studies), chronic steroid use (eight studies) and obesity (six studies) .…”
Section: Resultsmentioning
confidence: 98%
“…right hemicolectomy, total proctocolectomy (TPC), sigmoidectomy]. Two studies compared the types of operation being performed for IBD and CRC patients . There was no significant difference between laparoscopic and open approaches or for pelvic and abdominal operations between the two groups.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations